2016
DOI: 10.1152/jn.00951.2015
|View full text |Cite
|
Sign up to set email alerts
|

The sequential encoding of competing action goals involves dynamic restructuring of motor plans in working memory

Abstract: Gallivan JP, Bowman NA, Chapman CS, Wolpert DM, Flanagan JR. The sequential encoding of competing action goals involves dynamic restructuring of motor plans in working memory. J Neurophysiol 115: 3113-3122, 2016. First published March 30, 2016 doi:10.1152/jn.00951.2015.-Recent neural and behavioral findings provide support for the influential idea that in situations in which multiple action options are presented simultaneously, we prepare action plans for each competing option before deciding between and exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…A recent EEG study showed that in situations where different WM contents are associated with specific actions, the selection of taskrelevant sensory representations and appropriate motor plans may occur in parallel and not serially as would be expected if the WM code was primarily sensory in nature 13 . Instead, these results are consistent with a model of WM in which the brain, when possible, will link sensory representations to their motor plan to guide future behaviour, further integrating the WM literature to literature on motor planning 14,15 . However, many WM tasks, such as continuous report tasks 16 or change-detection tasks 7 , do not allow for motor preparation at encoding, but instead require a comparison between a WM stimulus and an unpredictable post-delay target.…”
Section: Introductionsupporting
confidence: 82%
“…A recent EEG study showed that in situations where different WM contents are associated with specific actions, the selection of taskrelevant sensory representations and appropriate motor plans may occur in parallel and not serially as would be expected if the WM code was primarily sensory in nature 13 . Instead, these results are consistent with a model of WM in which the brain, when possible, will link sensory representations to their motor plan to guide future behaviour, further integrating the WM literature to literature on motor planning 14,15 . However, many WM tasks, such as continuous report tasks 16 or change-detection tasks 7 , do not allow for motor preparation at encoding, but instead require a comparison between a WM stimulus and an unpredictable post-delay target.…”
Section: Introductionsupporting
confidence: 82%
“…Further support for this notion comes from prior investigations showing that it is possible to simultaneously plan reaching movements towards multiple target objects and to subsequently only select one out of the already planned movements 7,42,43 . Referred to the current experiment, the S-R mapping following a one-item retro-cue toward a red item would contain the following information: 'If the memory probe is red, press the left button, if not, press the right button'.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, Hommel, Müsseler, Aschersleben and Prinz 2 highlighted that a motor plan is a code of the perceptual consequences of a motor action rather than a conscious plan of a complex sequence of muscle tension and relaxation. Important for this account, working memory can not only actively store stimulus representations in different sensory stores 4,5 , but also higher-level representations of to-be-executed actions [6][7][8][9] . It is therefore reasonable to assume that the transition from purely sensory information to higher-level sensorimotor representations for guiding future actions proceeds in working memory.…”
Section: Introductionmentioning
confidence: 99%
“…Machens's study [35] shows that decision-making is controlled by memory signals, and that action control is achieved by mutual restraint between decision-making patterns. Gallivan's [36] research indicates that brain sequential decision-making is achieved through competition among decision-making patterns, which is accomplished by local inhibition between patterns. The experiments of Kuo's work [1] shows that there is a game relationship between controlled decision-making (memory-based decision-making) and stimulus response.…”
Section: Neural Architecturementioning
confidence: 99%